Role of adductor canal block and genicular nerve block on postoperative pain and enhanced recovery in patients undergoing total knee arthroplasty: A randomized clinical trial - Bassel Mohammed Elfokery; Mustafa Seet; Tareef Ashour; Hatem Alharbi; Mujeeb Ashraf; Hatim Alshareef; Mohammad Nyaz; Rayan Bakhreba; Atif Sait (Bali Journal of Anesthesiology)
Abstract Background: The postoperative pain management for total knee arthroplasty (TKA) remains controversial. This work aimed to assess the role of adductor canal block (ACB) and genicular nerve block (GNB) on postoperative pain and the possibility of enhanced recovery in patients undergoing TKA. Patients and Methods: This randomized trial was conducted on 50 subjects aged 40–75 years who underwent TKA under spinal anesthesia. The patients were divided into two equal groups: group A received an intraarticular injection of 40 mL bupivacaine 0.125% by the surgeon. Group B, in addition to the same intraarticular injection, also received pre-incision GNB (20 mL bupivacaine 0.25% and 8 mg dexamethasone) and ACB (10 mL bupivacaine 0.25% and 4 mg dexamethasone) at the end of surgery. We assessed postoperative pain up to 48 h postoperative, range of motion (ROM), and mobility status. Results: Subjects in group B showed lower Visual Analog Scale at rest and mobilization at 6 h (P < 0.001), 12 h (P = 0.005), 18 h (P = 0.001), and 24 h (P = 0.001). ROM was also significantly higher on postoperative day 1 (P = 0.022) and day 2 (P = 0.007) in group B. Similarly, the ability to walk with support on postoperative day 1 (P = 0.023) and day 2 (P = 0.037) and the ability to perform straight leg raising independently on day 1 (P = 0.038) and day 2 (P = 0.027) days were also notably better in group B. Finally, hospital stay was significantly lower in group B (P = 0.016). Conclusions: The combination of ACB and GNB provided adequate analgesia and enhanced recovery via reducing pain scores, total opioid consumption with shorter hospital stays, better mobility, and patient satisfaction.